Network Pharmacology-Based Investigation of the Molecular Mechanisms of the Chinese Herbal Formula Shenyi in the Treatment of Diabetic Nephropathy - Chen, Keng; Deng, Yiyao; Shang, Shunlai; Li, Ping; Liu, Linchang; Chen, Xiangmei (Frontiers in Medicine, 2022)
Background The Chinese herbal formula Shenyi (SY) is a prescription that was developed by the Department of Nephrology, Chinese People's Liberation Army General Hospital. This preparation is mainly used to treat chronic kidney disease (CKD) caused by Diabetic nephropathy (DN) and is effective. However, the active ingredients of SY, DN treatment-related molecular targets and the effector mechanisms are still unclear. Methods The Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and the Traditional Chinese Medicine and Chemical Component Database of Shanghai Institute of Organic Chemistry were used to screen the active ingredients in SY, the TCMSP database and Swiss Target Prediction database were used to collect the targets of the active ingredients of SY, and the Gene Cards and Online Mendelian Inheritance in Man (OMIM) databases were used to screen for DN pathogenesis targets. The intersections of the component targets and disease targets were mapped to obtain the therapeutic targets. The METASCAPE database was used to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of the therapeutic targets. Cytoscape 3.7.2 was used to analyze topological parameters and construct a network of SY for the treatment of DN. Results Sixty-two active ingredients and 497 active ingredient effector targets in SY, 3260 DN-related targets, and 271 SY treatments for DN targets were identified. Among these targets, 17 were core targets, including AKT1, tumor necrosis factor (TNF), interleukin-6 (IL6), and TP53. The GO and KEGG enrichment analyses show that SY's therapeutic effects for DN occur mainly through pathways such as advanced glycation end product (AGE)-RAGE, PI3K-Akt, and IL-17. Conclusion Multiple active ingredients in SY exhibit treatment effects on DN by affecting metabolism, inhibiting inflammation, and affecting cell structure growth.